MATHEMATICAL MODELING OF GREEN TARIFF ELECTRICITY BILLING IN A LAYER POULTRY FARM BASED ON CONSUMPTION INDICATORS - Christovão, Monclar N.; Cremasco, Camila P. [UNESP]; Neto, Mario Mollo [UNESP]; Filho, Luís R. A. Gabriel [UNESP] (FapUNIFESP (SciELO), 2023)
The increasing electricity consumption, inflated costs, and environmental restrictions drive the need for more efficient energy usage and the development of energy conservation programs. Many farms in Brazil produce their animal feed by crushing grains and cereals using electric motor-equipped devices. However, these motors are often oversized and operate during peak times, leading to increased production costs. This study aimed to mathematically model electricity billing under the green tariff (group A) for an egg production farm. The model incorporated mathematical equations based on selected electrical parameters such as load, power factors, energy demand, and active consumption. The Mathematica software was used to implement the proposed model. The farm provided the past twelve electricity bills, which were inputted into the software, generating three-dimensional surface graphics and contour maps. These visualizations revealed an inversely proportional relationship between bill prices and power/load factor indicators. This study concludes that the presented methodology can be employed by agribusiness companies to assess performance, explore alternatives, avoid potential fines, and optimize energy consumption.
Keywords: electricity bill simulation software; electricity billing; green hourly tariff; load factor; power factor